Rural Envoirment vis-a-vis Buffalo Husbandry: A Factor Analysis - Dixit, V.B.; Bharadwaj, A.; Laharia, S.N (Indian Journal of Extension Education, 2010)
The study was conducted in four districts of Murrah tract in Haryana. The sample constituted 200 farmers, 50 scientists and 50 veterinary surgeons. The buffalo husbandry practices, which affect rural environment, were identified. Based on the perceptions of farmers, scientists and veterinary surgeons 34 environmental problems related to buffalo husbandry were identified. The response of scientists and veterinary surgeons for these problems was elicited on 5 point continuum and was subjected to factor analysis. On the basis of this analysis 6 factors which contributed significantly to the variance were finally identified. Changing paradigm of development demands increasing concern about environmental degradation. Environmental pollution is a very serious threat to mankind. Its gravity in urban areas and industrial belts has been widely recognized. However, its problems in rural areas where still more than two third population of the country lives, has failed to get the attention. There may be several reasons for this problem in the villages, which may vary from region to region depending upon agro-climatic conditions, geographic location, socio-economic status etc.